Gibt es eine „Zweite Moderne“?: über den Umgang mit soziologischen Diagnosen - Schwinn, Thomas (Soziale Welt, 1999)
Sociology presents diagnoses of our time in ever new abundance: postmodernity, second modernity, world society, individualization, etc. This indulgence in producing diagnoses of our time stands in sharp contrast to the discipline's poor capacity for predicting important events and upheavals that occurred in the past. The article takes Ulrich Beck's thesis of a 'second modernity' to illustrate how to deal with such a diagnosis that leads to rather compact predictions. The theorem of 'second modernity' is reduced to scientifically workable core theses about which reasonable statements can be made. Beck argues that present-day problems, especially ecological problems, fall through the grid of the existing differentiated institutions and rationalities and that a synthesis or a mix of rationalities is required in order to cope with the overlapping problems that don't fit into the differentiation. The article doubts that a 'second modernity' is rising and that a mix of rationalities is needed. For this we have to distinguish between rationalities and institutions.